Slow Science and Slow Education in a Digitalized University: an Anthropopractic Approach - Yu. A. Gorbunova; I. O. Boronikhina (Дискурс)
Introduction. The slow movement in universities is a reaction to the economic-centricity and commodification of higher education and science, the standardization and quantifiability of research and educational activities, the expansion of digital technologies` use in the generation and assimilation of knowledge, the imposition of the cult of speed on the academic and student communities. Rapid knowledge practices are becoming a trend in the context of digitalization of higher education. At the same time, the slow movement in Russian universities remains marginal and poorly institutionalized. The article analyzes the philosophical concepts that underlie the slow movement in universities and substantiates the importance of an anthropopractical approach to the study of slow science and slow education.Methodology and sources. The technocratic approach to the digitalization of higher education contributes to the spread of high-speed science and learning practices based on the reduction of knowledge to information, the growth of knowledge – to extension and cumulation, the cognitive motivation – to competition, greed and ambition. Turning to an anthropopractic approach allows us to overcome this reductionism. Slow science and slow education as anthropological practices are based on the desire of subjects of cognition for dialogue, reflection, improvisation and creative self-realization, self-organization and autodesign, intellectual enjoyment, sustainable, ecological coexistence. Digital technologies are only driving tools for this practice.Results and discussion. Slow practices in education and science are considered in this article, firstly, as an antithesis to the practices of posthumanism and futuro design, overcoming imperfect human nature and movement towards a posthuman with the help of nano-, bio-, information, cognitive and social technologies. Secondly, slow science and slow education as anthropological practices are opposed to managerial practices that form educational environments hostile to a person, the characteristic features of which are competition and hierarchy in the system “effective – ineffective”, “winners – losers”, “successful – catching up – lagging behind”. Conclusion. The authors see the optimal scenario for the transfer of slow practices to the sphere of higher education in Russia in achieving a balance between pragmatism, a shortterm policy and effectivenes, and a reflective position that ensures an anthropological orientation and sustainable development of modern universities.